Degradation of Acid Orange II by Heterogeneous Fenton-like Reaction Using Clay Supported Fe3-xMoxO4 Composite Catalyst - Alrozi, Rasyidah; Aida Zubir, Nor; Aina Jumain, Aisyah; Shafika Zainun, Norhamimi; Khairul Azam Selamat, Mohammad; Nasuha, Norhaslinda; Imam Maarof, Hawaiah; Anuar Kamaruddin, Mohamad (International Journal of Engineering and Technology, 2018)
In this study, investigations on four different types of clays as catalyst support and the influence of its loading in relation with catalytic performance of the resultant composite catalysts are performed. The inherent catalytic activity of MKSF, MK10, bentonite and kaolin as catalyst supports have been tested in the oxidative degradation of AOII as the model pollutant. The highest AOII degradation was exhibited by MKSF that followed by bentonite, kaolin and MK10. Therefore, MKSF has been chosen as the catalyst support to immobilize the active sites of Fe3-0.4Mo0.4O4 catalyst. The MKSF loading were varied at x = 0, 20, 40, 60 and 80 wt%, respectively. Interestingly, Fe3-0.4Mo0.4O4-MKSF(80wt%) has shown superior catalytic performance up to 98.8% of AOII removal in comparison to the Fe3O4 and Fe3-0.4Mo0.4O4 catalysts. Meanwhile, the second-order reaction kinetic model well described AOII degradation and its rate increased in the order of Fe3O4>Fe3-0.4Mo0.4O4>Fe3-0.4Mo0.4O4-MKSF(80wt%). Hence, these findings prove that having MKSF clays as catalyst support provides a positive influence in enhancing the overall catalytic performance of Fe3-0.4Mo0.4O4 catalyst during the Fenton-like reaction as well as the degradation kinetics of the AOII solutions.Â Â